2021
DOI: 10.1161/strokeaha.120.032723
|View full text |Cite
|
Sign up to set email alerts
|

Race Differences in High-Grade Carotid Artery Stenosis

Abstract: Background and Purpose: Despite a higher incidence of stroke and a more adverse cardiovascular risk factor profile in Blacks and Hispanics compared with Whites, carotid artery revascularization is performed less frequently among these subpopulations. We assessed racial differences in high-grade (≥70% diameter-reducing) carotid stenosis. Methods: Consecutive clients in a Nationwide Life Line for-Profit Service to screen for vascular disease, 2005 to 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…3 Unfortunately, it had been showed that the carotid stenosis increased consistently with age, and the prevalence of >50% carotid stenoses among ≥80 years of patients was 7.5% and 5.0% for males and females respectively. 2,29,30 In addition, ICAS is more prevalent in the aged and in Asians. [31][32] The current studies and guidelines do not support the percutaneous intracranial stenting and EC-IC employed as first-line treatment in patients with ICAS.…”
Section: Discussionmentioning
confidence: 99%
“…3 Unfortunately, it had been showed that the carotid stenosis increased consistently with age, and the prevalence of >50% carotid stenoses among ≥80 years of patients was 7.5% and 5.0% for males and females respectively. 2,29,30 In addition, ICAS is more prevalent in the aged and in Asians. [31][32] The current studies and guidelines do not support the percutaneous intracranial stenting and EC-IC employed as first-line treatment in patients with ICAS.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with prior reports, when evaluating underrepresented groups defined by race and ethnicity, we found that Black and Hispanic participants had a lower prevalence of CAS. 1,2 Moreover, Black participants had lower estimates of carotid revascularization, which could be explained by lower rates of high-grade stenosis, 1 but other factors should be explored further, including the potential presence of care access bias. Of note, our study may be subject to volunteer bias, leading to an increased number of healthy people enrolled.…”
Section: Discussionmentioning
confidence: 99%
“…There are marked differences in the prevalence of carotid artery stenosis (CAS) and revascularization among underrepresented groups defined by race and ethnicity. 1,2 It is increasingly recognized that underrepresented groups defined by factors other than race and ethnicity also carry a disproportionate burden of cardiovascular disease. 3 We used the All of Us Research Program 4 to test the hypothesis that the burden of CAS and the proportion of persons who undergo carotid revascularization differ in broadly defined underrepresented groups.…”
mentioning
confidence: 99%
“…9 Non-Hispanic White individuals might be at a greater risk of developing lipoprotein-rich carotid plaques than Black individuals regardless of lipoprotein levels. [10][11][12] A study conducted on a semi-rural population of Black and White individuals found a cross-sectional association between cIMT and cognitive performance in midlife that was stronger in Black than in White individuals. 13 On the other hand, a cross-sectional analysis of a population-based cohort study, which included African American and non-Hispanic White individuals, verified a stronger association between greater cIMT and lower cognitive function in non-Hispanic White individuals and in participants with higher socioeconomic status, which points to inconsistent findings on the modifying effect of race on the relationship between cIMT and cognitive performance.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of carotid atherosclerosis differs by race/ethnicity 9 . Non‐Hispanic White individuals might be at a greater risk of developing lipoprotein‐rich carotid plaques than Black individuals regardless of lipoprotein levels 10–12 . A study conducted on a semi‐rural population of Black and White individuals found a cross‐sectional association between cIMT and cognitive performance in midlife that was stronger in Black than in White individuals 13 .…”
Section: Introductionmentioning
confidence: 99%